Verification of a standardized method for inserting intramuscular electromyography electrodes into teres minor using ultrasound. Issue 6 (14th May 2015) - Rathi, Sangeeta; Zacharias, Anita; Green, Rodney A.
<x xml:space="preserve">Abstract</x> The close proximity of the infraspinatus to the teres minor and their functional similarity in producing external rotation of the glenohumeral joint make accurate insertion of electromyographic (EMG) electrodes into the teres minor difficult and questionable even when published guidelines are followed. The primary aim of this study was to examine the anatomical support for the current guidelines for inserting intramuscular EMG electrodes into the teres minor muscle. The secondary aim was to provide a technical description for ultrasound‐guided electrode insertion into the teres minor. Intramuscular electrodes were inserted into four cadaveric shoulders using markings based on the current guidelines. EMG electrodes were also inserted into the teres minor of four healthy male participants using real‐time ultrasound (RTUS) guidance. Systematic dissections of the cadaver specimens revealed that the electrode had been successfully inserted into the teres minor muscle in only one out of the four. In the remaining three specimens, the needle lodged in the infraspinatus muscle belly at distances ranging from 3 to 17 mm medial to the teres minor. Using RTUS guidance, the electrodes were successfully inserted into the teres minor in all participants, as confirmed by visual inspection with RTUS. This study confirms that the current EMG electrode insertion guidelines for the teres minor are not accurate and RTUS ensures the placement of electrodes into the teres minor rather than the adjacent infraspinatus muscle. Clin. Anat. 28:780–785, 2015. © 2015 Wiley Periodicals, Inc.